Study on "Two Zone" Development Height of Overburden Rock in Fully Mechanized Face with Large Mining Height. Issue 1 (June 2020) - Du, Mingze; Kong, Fanlong; Wang, Donghao
Abstract: In terms of the problems of the development height of the "two zones" of overburden in the fully mechanized mining face was difficult to predict, taking the 31303 working face in Chahasu coal mine as an example, methods of empirical formula, leakage of drilling fluid and borehole colour TV were used for prediction and exploration. On the basis, the concept of empirical formula error was proposed, and the error rate predicted by slicing mining and fully mechanized caving mining in thick seam was analysed. The results showed that the fracture-mining ratio and caving-mining ratio of 31303 working face were 23.67 and 5.6 respectively, that is, the development height of water-conducting fracture zone and caving zone were 106.50 m and 25.20 m respectively. The "two zones" empirical formula of thick seam slicing mining and fully mechanized caving mining deviated greatly from the predicted results of fully mechanized mining face with large mining height. The formula for calculating the error rate of empirical formula was proposed. The error rates of the empirical formulas for layered mining and fully mechanized caving mining were quantitatively analysed, which were 50% and ± 28%, respectively, indicating that the traditional empirical formula was not universal in the prediction of "two zones" of fully mechanized mining with slicing mining.